Efek Pemberian Kulit Jeruk Berastagi (Citrus Sinensis L) Secara Topikal Terhadap Perbaikan Luka Sayat Tikus Berdasarkan Jumlah Fibroblast dan Diameter Luka - Sumantri, Dinda Triana; Natali, Oliviti; Lubis, Adhayani; Perangin-Angin, Eka Lestari Br; Jelita Siregar, Yohana Putri (Syntax Literate, 2025)
Wound healing is a complex biological process involving cellular and tissue responses, including fibroblast formation and wound diameter closure. Berastagi orange peel extract (Citrus sinensis L.) contains flavonoids, tannins, and vitamin C, which play roles in anti-inflammatory, antioxidant, and collagen-stimulating processes, thus potentially accelerating wound healing. This study aimed to determine the effect of topical administration of Berastagi orange peel extract (Citrus sinensis L.) on the healing of incised wounds in rats based on fibroblast count and wound diameter. This research employed a quantitative analytic true experimental design with a post-test group design. Rats were divided into several treatment groups, namely gel base, 10% povidone iodine, and Berastagi orange peel extract gel (EEKJ) at concentrations of 40%, 60%, and 80%. The observed parameters were fibroblast count and wound diameter on day 0 and day 14. Data were analyzed using ANOVA followed by Post Hoc tests. The results showed an increase in fibroblast count and a greater reduction in wound diameter in the groups treated with EEKJ gel compared to the gel base control group. Compared to 10% povidone iodine, EEKJ gel also showed relatively comparable effects in accelerating wound healing. The 60% concentration demonstrated more optimal results in stimulating fibroblast proliferation and reducing wound diameter, although statistically, the differences between concentrations were not significant (p > 0.05). Topical administration of Berastagi orange peel extract proved effective in accelerating the healing process of incised wounds by increasing fibroblast count and reducing wound diameter. The 60% concentration was the most optimal compared to other concentrations, although the differences were not statistically significant.